2017
DOI: 10.14740/wjnu317w
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D With Prostate Carcinoma: A Single Institutional Observational Study

Abstract: Background: Recent studies highlight a role for vitamin D (VD) in the growth and differentiation of various cell types. The biologically active form of vitamin D3 is 1,25-dihydroxyvitamin D3. Most cells of the body including prostate cells have vitamin D receptor (VDR) and VD metabolizing enzymes, and can respond to 1,25-VD. Literature supports multipronged effects of 1,25-VD in the prevention of prostate carcinoma development and progression. However, the relationship between prostate carcinoma and VD is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
2
2
Order By: Relevance
“…Thus, it was observed that there is no clear association between vitamin D deficiency and prostate cancer. This observation was contrary to the study carried out by Choubey et al 15 where they found that the cases had lower vitamin D levels (10.1 ± 6.4 ng/mL) but the controls had normal vitamin D levels (23.2 ± 8.9 ng/mL). A retrospective analysis by Yaturu et al 16 involving 479 cases and 473 controls also suggested that there was no statistically significant difference in serum vitamin D level and prostate cancer as levels of serum vitamin D were 47.2 ± 6.8 ng/mL and 47.1 ± 7.11 ng/mL in cases and controls, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, it was observed that there is no clear association between vitamin D deficiency and prostate cancer. This observation was contrary to the study carried out by Choubey et al 15 where they found that the cases had lower vitamin D levels (10.1 ± 6.4 ng/mL) but the controls had normal vitamin D levels (23.2 ± 8.9 ng/mL). A retrospective analysis by Yaturu et al 16 involving 479 cases and 473 controls also suggested that there was no statistically significant difference in serum vitamin D level and prostate cancer as levels of serum vitamin D were 47.2 ± 6.8 ng/mL and 47.1 ± 7.11 ng/mL in cases and controls, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, it was observed that there is no clear association between vitamin D deficiency and prostate cancer. This observation was contrary to the study carried out by Choubey et al 15 where they found that the cases had lower vitamin D levels (10.1 ± 6.4 ng/mL) but the controls had normal vitamin D levels (23.2 ± 8.9 ng/mL).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Many cross‐sectional and retrospective studies associate vitamin D deficiency and insufficiency with prostate cancer mortality and, specifically, with aggressive prostate cancer (Choubey et al, 2017; Kumawat et al, 2021; Murphy et al, 2014; Özman et al, 2021; Xie et al, 2017). This association appears to be valid in middle‐income countries but not necessarily as evident in high‐income countries (Stanaland et al, 2017; Trump et al, 2009; Yaturu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%